ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2020
DOI: 10.1109/icassp40776.2020.9053125
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Transport Structure of CycleGAN for Unsupervised Learning for Inverse Problems

Abstract: The penalized least squares (PLS) is a classic approach to inverse problems, where a regularization term is added to stabilize the solution. Optimal transport (OT) is another mathematical framework for computer vision tasks by providing means to transport one measure to another at minimal cost. Cycle-consistent generative adversarial network (cycleGAN) is a recent extension of GAN to learn target distributions with less mode collapsing behavior. Although similar in that no supervised training is required, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…An alternative approach, which assumes the same data are acquired with two separate acquisitions using different undersampling patterns, was also proposed, 63,64 extending on the Noise2Noise denoising framework 65 . In the same image‐domain reconstruction setting, a self‐supervised learning scheme using cycleGANs with optimal transport cost minimization was proposed, 66 although initial results exhibit blurring artifacts. Although purely data‐driven image domain methods have been used for DL‐MRI reconstruction, physics‐guided DL‐MRI techniques are more desirable, as they offer a degree of interpretability by incorporating domain knowledge on the MRI encoding mechanism 20,27,28,30,31,33 .…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach, which assumes the same data are acquired with two separate acquisitions using different undersampling patterns, was also proposed, 63,64 extending on the Noise2Noise denoising framework 65 . In the same image‐domain reconstruction setting, a self‐supervised learning scheme using cycleGANs with optimal transport cost minimization was proposed, 66 although initial results exhibit blurring artifacts. Although purely data‐driven image domain methods have been used for DL‐MRI reconstruction, physics‐guided DL‐MRI techniques are more desirable, as they offer a degree of interpretability by incorporating domain knowledge on the MRI encoding mechanism 20,27,28,30,31,33 .…”
Section: Discussionmentioning
confidence: 99%
“…We compute a consistency loss in k-space as it was also suggested in [9]. An alternative is to apply it in image domain as in [16]. We found that the two methods are not fundamentally different and in simulations they behave very similarly.…”
Section: Data Consistencymentioning
confidence: 99%
“…2. Comparison of 8× accelerated MRI reconstructions; first) zero-filled, second) CycleGAN-unsup [16], third) LCFI++ (ours) with half of the dataset, fourth) MICCAN [17], fifth) CycleGAN-sup [16], sixth) LCFI++ (ours), and last) ground truth. [17].…”
Section: Qualitative Analysismentioning
confidence: 99%
See 2 more Smart Citations